A novel strategy for the discovery of MHC class II-restricted tumor antigens: identification of a melanotransferrin helper T-cell epitope - Röhn, Till Alexander; Paschen, Annette; Nguyen, Xuan-Duc; Schadendorf, Dirk (Cancer research, 2005)
CD4+ helper T cells play a critical role in orchestrating host immune responses, including antitumor immunity. The limited availability of MHC class II-associated tumor antigens is still viewed as a major obstacle in the use of CD4+ T cells in cancer vaccines. Here, we describe a novel approach for the identification of MHC class II tumor-associated antigens (TAAs). By combining two-dimensional liquid chromatography and nanoelectrospray ionization tandem mass spectrometry, we developed a highly sensitive method for the detection of human leukocyte antigen (HLA)-DR-associated peptides of dendritic cells upon exposure to necrotic tumor cells. This approach led to the identification of a novel MHC class II-restricted TAA epitope derived from melanotransferrin. The epitope stimulated T cells derived from melanoma patients and healthy individuals and displayed promiscuity in HLA-DR restriction. Moreover, the same peptide was also presented by MHC class II-positive melanoma cells. This strategy may contribute to increase the number of tumor epitopes presented by MHC class II molecules and may support the development of more efficacious vaccines against cancer.